Clinical and laboratory features of infectious mononucleosis in children of early age - Колесник, Ю.; Кузнєцов, С.В.; Губар, С.О.; Жаркова, Т.С.; Kolesnyk, Y.; Kuznetsov, Sergii; Gubar, Sergii; Zharkova, T. (ХНМУ, 2020)
In the world infectious mononucleosis (IM) annually affects from 16 to 800 persons per 100 thousand population. According to the WHO, more than 50% of children of the first 10 years and 80-90% of adults have specific antibodies to the virus as a marker of previous infection. The infection rate of the adult population of Ukraine is almost 100%, and infection rate of the children is more than 50%, wherein 50% of them have a relapsing course of the disease. The significance of the problem of IM in the world is due not only of prevalence, but also is due to severe consequences, complications and deaths caused by to the development of lymphoproliferative diseases.
Keywords: infectious mononucleosis; children